The Library of James Marsh, DD (1593-?1645), with ‘Shackspeers playes’ and ‘Donnes Poem’ - Higgins, Ben (Library, 2021)
Abstract This essay provides a case study of an otherwise-unknown clerical library from the 1640s that includes a copy of a Shakespeare folio alongside a few other literary works, including John Donne's Poems (1633). The essay offers a biography of the library's owner, a sketch of the library as a whole, and concludes by considering the unusual status of the Shakespeare folio in this collection. An appendix transcribes the inventory in which the library is catalogued. In this collection of around 200 books, the Shakespeare folio was the sole book of drama (either vernacular or classical). James Marsh is thus an outlier in what we know about early folio-ownership and the discovery of his library expands our understanding of the contexts in which Shakespeare was owned and read.